#### Answer

$(3x-\sqrt{2})(3x-\sqrt{2})=9x^{2}-6x\sqrt{2}+2$

#### Work Step by Step

$(3x-\sqrt{2})(3x-\sqrt{2})$
Rewrite this expression as $(3x-\sqrt{2})^{2}$:
$(3x-\sqrt{2})(3x-\sqrt{2})=(3x-\sqrt{2})^{2}=...$
Use the formula for squaring a binomial to evaluate this power. The formula is $(a-b)^{2}=a^{2}-2ab+b^{2}$.
For this particular case, $a=3x$ and $b=\sqrt{2}$
Substitute the known values into the formula and simplify if possible:
$...=(3x)^{2}-2(3x)(\sqrt{2})+(\sqrt{2})^{2}=9x^{2}-6x\sqrt{2}+2$